The 28-day oral toxicity of the extract of Silybum marianum in rats - JI Hainan; ZHAO Chan; LIN Zijun; TONG Na; CHEN Bowen; ZHOU Shimeng; LIU Mingchang; SHEN Guolin; ZHANG Mengling (Shipin yu jixie)
ObjectiveThis study aimed to assess the 28-day oral toxicity of Sihbum manalttlm extract in rats.MethodsSD rats were administered S. manalttlm extract, and effects on body weight, organ coefficients, biochemical indicators, blood routine and hemagglutination indicators, and liver pathology were evaluated to determine safety.ResultsS. manalttlm extract showed no adverse effects on body weight, organ coefficients, biochemical indicators, blood routine and coagulation indicators, or liver pathology. Additionally, S. manalttlm extract appeared to positively influence pathways related to plasma amino acid metabolism, liver riboflavin metabolism, carbohydrate metabolism, and sphingolipid metabolism, contributing to overall health benefits in rats.ConclusionS. manalttlm extract was deemed safe Under the dosage and conditions of this study.